Work-Integrated Learning in a Changing Educational Context - Mudaly, Vimolan (Research in Social Sciences and Technology, 2025)
Teaching, while acknowledged to be a noble career, can be a very difficult path. Preservice teacher educators are tasked with the immense duty of transforming preservice teachers into pedagogues that could and should make a difference to the lives of those they interact with. As teacher educators, we must strive to create continuing support and shared accountability, so that preservice teachers will be empowered as effective educators to extend themselves to ensure that the learners at schools attain their highest goals. This research looked at the way Work Integrated Learning (WIL) aides in this process. After the necessary ethical issues were addressed and permission obtained to conduct the study, final-year undergrad students, inservice teachers, and staff were encouraged to participate in this interpretative study. They were required to respond to an online questionnaire and a sample of participants was interviewed. The results are not unexpected and reinforce the idea that WIL learning has to adapt to the evolving technological culture that pervades all of society.